Efektivitas Pelaksanaan Kuliah Kerja Nyata Mahasiswa Universitas Negeri Padang Tahun 2022 - Syamtya Ego; Habibullah Habibullah (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research was conducted to find out how effective the implementation of real-work lectures for Padang State University students is. This research is descriptive research that uses a quantitative method approach, where the researcher conducts this research using a questionnaire or questionnaire which the researcher will later distribute to the respondents. Respondents in this study were students of the Electrical Engineering Education Study Program (S1) and Industrial Electrical Engineering (D4) batch 2018 and 2019 who had finished carrying out real work lectures. This research was chosen by the researchers because they intend to collect accurate information and data in a structured manner regarding facts about the effectiveness of implementing real work lectures for Padang State University students. Assessment of research instruments using a Likert scale. In this study, descriptive statistics were used to present data that had been obtained in the field in tabular form in the form of average values ​​(mean), median scores (mode), standard deviation (standard deviation), and minimum score (minimum score). score), maximum score (maximum score), and total score (sum). The formula used to analyze the data in this study is the degree of attainment (DP). From the results of the overall calculation, the results obtained for measuring the degree of achievement (DP)variable the effectiveness of the implementation of real work lectures for Padang State University students was 79.26% in the pretty good category.